Efficient synthesis of O-aryloxime ethers by copper fiuorapatite catalyzed cross-coupling of aryloximes with arylboronic acids - Mulla, Shafeek Abdul Rashid; Chavan, Santosh S.; Inamdar, Suleman M.; Pathari, Mohsinkhan Y.; Shaikh, Taufeekaslam M. Y. (Tetrahedron Letters, 2014)
A novel, highly efficient, and mild protocol has been developed for the synthesis of O-aryloxime ethers in good to excellent yields at ambient reaction conditions. This is the first report in which =N-O-Ar linkage was achieved with ecofriendly, recyclable, heterogeneous copper fluorapatite (CuFAP) catalyst via C-O cross coupling of aryloxime with arylboronic acid in the presence of Cs2CO3 as base and methanol as solvent. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Arylboronic acid; Aryloxime; Copper fluorapatite; O-Aryloxime ethers